Identification of a pluripotency-inducing small compound, PLU, that induces callus formation via Heat Shock Protein 90-mediated activation of auxin signaling - Nakashima, Yuki; Kobayashi, Yuka; Murao, Mizuki; Kato, Rika; Endo, Hitoshi; Higo, Asuka; Iwasaki, Rie; Kojima, Mikiko; Takebayashi, Yumiko; Sato, Ayato; Nomoto, Mika; Sakakibara, Hitoshi; et al. (Frontiers in Plant Science, 2023)
Plants retain the ability to generate a pluripotent tissue called callus by dedifferentiating somatic cells. A pluripotent callus can also be artificially induced by culturing explants with hormone mixtures of auxin and cytokinin, and an entire body can then be regenerated from the callus. Here we identified a pluripotency-inducing small compound, PLU, that induces the formation of callus with tissue regeneration potency without the external application of either auxin or cytokinin. The PLU-induced callus expressed several marker genes related to pluripotency acquisition via lateral root initiation processes. PLU-induced callus formation required activation of the auxin signaling pathway though the amount of active auxin was reduced by PLU treatment. RNA-seq analysis and subsequent experiments revealed that Heat Shock Protein 90 (HSP90) mediates a significant part of the PLU-initiated early events. We also showed that HSP90-dependent expression of TRANSPORT INHIBITOR RESPONSE 1, an auxin receptor gene, is required for the induction of callus formation by PLU. Collectively, this study provides a new tool for manipulating and investigating the induction of plant pluripotency from a different angle from the conventional method with the external application of hormone mixtures.